Internationalisation of companies and local upgrading of peripheries - The Example of VW Navarre in the European automobile production system - Martina Fuchs (European Regional Science Association (ERSA), 2005)
Recently we find two main issues in the current debate on globalized localities: the first issue concerns itself with the fragmentation and relocation of value chains, chain governance and upgrading, focussing on supply chains between different companies. The second is about the division of labour and knowledge inside of transnational companies. The first perspective has developed new theoretical concepts, inspired by Gereffi, and now already more differentiated with regard to the question what "upgrading” of periphal companies can mean. The publication of Schmitz (ed., 2004) offers a view on the state of the art, which is related to conceptual work and case studies about market relations (arm's length relations), networks (reciprocal dependencies) and quasi-hierarchies (control in supply chains). Hierarchical relations (between parent companies and their subsidaries) are not included. This may be a result of the starting point of the value chain discussion, but obviously there is a research gap. The upgrading perspective is interesting for enterprise geography, because it gives a chance to develop a deeper understanding of 'local knowledge'. Often, we focus on R&D, but for local development, R&D is only one aspect of many. Furthermore, the international division of R&D only offers a technological, incremental view on the distribution of knowledge, but it excludes the perspective on power and governance. Moreover, a set of other aspects can be derived from the value chain debate, i.e. a differentiated understanding of the various kinds of product and process upgrading, functional and intersectoral upgrading. From the contributions in Schmitz (2004 ), we can learn to what extent and under which circumstances such upgrading really brings a better position for the locality or the region – and under which conditions not (i.e. cases of "running to keep the position” in the global competition). This paper tries to rule out the conceptual approach of upgrading on the background of the value chain approach, including insights of further research of enterprise geography. Enterprise geography can offer interesting insights for further conceptual work especially on "upgrading” and thus can give inputs for the interdisciplinary value chain debate. On the background of a case study of the European automobile industry, the paper discusses "upgrading” in a transnational company. With a closer view on Volkswagen, we will see that the concept of "upgrading” helps to understand the division of competences in a transnational company in a better way und thus offers new insights into the topic of hierarchies between plants and regions.
Keywords: 330